The 2019 Social Protests in Latin America: Global Context and Ecuadorian Case-Study - A. N. Pyatakov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2020)
The paper examines the phenomenon of global social protests that spread in 2019 across more than 20 countries. The author considers the most striking manifestations of this phenomenon that occurred in the Middle East, North Africa, Western Europe, and Asia. The paper provides a periodization of several waves of anti-globalization movement in the 21st century, whereby the current global unrest represents the third wave. The author identiﬁes speciﬁc features of each stage and outlines a growing trend towards politicization and exacerbation of violence. Particular emphasis is made on how the protests in Latin America developed in time and space, as they spread to at least eight states of the region: Haiti, Puerto Rico, Venezuela, Ecuador, Peru, Bolivia, Chile, and Columbia. In each country, protests were triggered by a peculiar set of internal factors which are not susceptible to easy generalization. In order to come nearer to the understanding of the new global phenomenon the author puts forward several socio-philosophical hypotheses. In particular, the possibility of internationalization of the French ‘yellow vests’ movement, its transfer and adaptation to other countries aﬀected by protests, is noted. In that regard the paper outlines certain ‘channels’ for exporting the French protests to Latin America, including migration and cultural ties. The author stresses that although socio-economic explanations of the global protest phenomenon that focus on such issues as the growth of inequality and social polarization, are correct, they are insuﬃcient for a comprehensive understanding of the new and complex phenomenon. As an alternative, the author suggests using the concept of ‘social singularity’. The paper considers the key features of this concept, including the idea that contemporary global social sphere is functioning in an online mode, allowing for increased speed of social interaction and communication on a global scale. Finally, the paper examines the causes and the development of the social unrest that broke out in Ecuador and served as a starting point for escalating the protest movement in Latin America in 2019.